INFLUENCE OF COMBINED USE OF PROBIOTIC AND ANTITOXICANT ON LIPID AND HEMATOLOGICAL STATUS AFTER NICKEL INTOXICATION IN THE BACKGROUND OF EXPERIMENTAL ATHEROSCLEROSIS - Ibragimov, R.I.; Ibragimova, N.I. (World of Medicine and Biology, 2024)
Metal exposure is a recently recognized risk factor for cardiovascular disease and is associated with the progression of atherosclerosis. There are data on the biotoxic effect of heavy metals on the hematological status and intestinal microbiota. In this study was studied the effectiveness of the combined use of a probiotic and a plant antitoxicant on the state of lipid and hematological status in conditions of chronic nickel poisoning against the background of experimental atherosclerosis. The results of the study showed that the experimental therapy reduced the severity of disturbances in the lipid and hematological status: the content of high-density lipoproteins increased and the atherogenicity index significantly decreased, as well as a tendency to normalize the level of reduced hemoglobin and mid-cell hemoglobin in erythrocytes. The data obtained show the feasibility of combined use of a probiotic and a plant antitoxicant in the complex therapy of chronic nickel poisoning through drinking water, which is especially important for patients with atherosclerotic vascular lesions.
Keywords: lipid and hematological status; nickel; experimental atherosclerosis; probiotic; antitoxicant